Reproduccion de Meloidogyne incognita en varias malezas presentes en Costa Rica - Lopez, R.=700 1 Quesada, M.
(En, Es)
ilus., 7 ref.
Keywords: MELOIDOGYNE INCOGNITA; MALEZAS; ESCARDA; ANTAGONISMO; COMPETENCIA BIOLOGICA; COSTA RICA